The effects of gender equality on economic development in Europe - Litmeyer, Marie-Louise; Bender, Leah; Happel, Sina; Peusch, Alex; Spory, Nicola; Hennemann, Stefan (ERDKUNDE, 2022)
Gender equality is increasingly perceived as a central issue and discussed as an essential factor for competition, economic growth and solidarity in society. The starting point of this study is the identification of the main factors influenced by gender equality in the context of the economic performance of countries. Europe was chosen as the study area, with regional differences between Northern, Western/Central, Southern and Eastern Europe also being taken into account. The empirical analysis is based on panel regression models. These confirm that policies designed to increase the share of women in leadership positions and to achieve an equal representation of self-employed women and men have a significant positive impact on a country’s economic performance across Europe. In addition, differentiated recommendations for action are derived from the results for the individual subregions.